Telemedicine‐guided remote enrollment of patients into an acute stroke trial. (17th December 2014) - Wu, Tzu‐Ching; Sarraj, Amrou; Jacobs, Amber; Shen, Loren; Indupuru, Hari; Biscamp, Donna; Ho, Victor; Ankrom, Christy; Grotta, James C.; Savitz, Sean I.; Barreto, Andrew D.
Abstract Background and Purpose Enrollment into acute stroke clinical trials is limited to experienced tertiary centers with emergency research infrastructure. Feasibility of remote enrollment via telemedicine into an acute thrombolytic clinical trial has never been demonstrated. Methods Using telemedicine, our hub stroke research center partnered with two spoke community hospitals to jointly participate in a randomized, phase III adjunctive thrombolysis clinical trial in the first 3 h after symptom onset to expand recruitment of the trial. Eligible patients were successfully identified, consented, randomized, and received therapy/placebo at the spoke hospitals under real‐time direction by hub trialists via telemedicine. Results Ten patients were identified from May 2013 to July 2014, and six were enrolled via telemedicine. No study procedure delays, safety events, or major protocol violations occurred. Conclusions It is feasible to randomize and enroll stroke patients via remote telemedicine into an acute thrombolytic clinical trial. This novel approach could expand access and accelerate completion of clinical trials if widely implemented.